Conceptions of Learning Among the Sudanese Students in Universiti Putra Malaysia - Mohamed, Mahasin Gadalla (1999)
The main point of the study is that human learning should be studied from a second-order perspective. Twenty-five post-graduate Sudanese students from various faculties at Universiti Putra Malaysia were asked about their view of learning. The qualitative data that has been acquired were analysed by using the inductive process known as phenomenography. The result of the analysis has identified four categories of learning conceptions: 1. acquisition of knowledge, 2. application of acquired knowledge, 3. understanding, and 4. changing human behaviour. Most of the subjects in this study fall under the third and fourth categories that are, understanding and changing human behaviour respectively. In the third category, the subject goes deeply into the meaning of what he learned, so learning in this category is an active process that involves looking deeply into the materials. In the fourth category, the change occurs due to the knowledge that was acquired by the person.